Sodium–glucose cotransporter-2 inhibitors improve cardiovascular outcomes post-acute coronary syndrome complicated by acute heart failure - Rahhal, Alaa; Hamamyh, Tahseen; Chapra, Ammar; Zaza, Khaled J.; Najim, Mostafa; Hemadneh, Mohammad; Faraj, Hazem; Kanjo, Wael; Yasin, Ahmed; Toba, Haneen; Mohammed, Wafa; Hamad, Mohammad Khair; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background Acute coronary syndrome (ACS) remains a risk factor for heart failure (HF). Therefore, we aimed to assess the cardioprotective role of sodium–glucose cotransporter-2 (SGLT2) inhibitors post-ACS in patients with acute HF (AHF) and diabetes. Methods We conducted a retrospective observational cohort study employing propensity score matching. This study involved patients with diabetes admitted with ACS complicated by AHF, defined as either new clinical HF requiring diuretics during the index admission or having an ejection fraction (EF) of <40%. The study population was divided into two groups; (1) SGLT2 inhibitor users and (2) SGLT2 inhibitor non-users. The Cox proportional hazard regression analysis was used to evaluate the outcomes. Results A total of 465 patients (93% male; mean age, 55 ± 10 years) were included in this study. Using a 1 : 1 propensity score matching, 78 patients were included per arm with an absolute standardized difference of <0.1 for all baseline characteristics. The use of SGLT2 inhibitors resulted in lower composite outcomes of ACS, HF hospitalization, and all-cause mortality at 1 month and 12 months [1 month: 2.6% vs. 11.5%, HR = 0.20 (0.04–0.94), p = 0.041; 12 months: 14.1% vs. 23.1%, HR = 0.46 (0.22–0.99), p = 0.046]. Conclusion The findings suggest that SGLT2 inhibitors may confer cardioprotective effects in ACS-induced AHF, thereby widening the spectrum for indications of SGLT2 inhibitors.